Defensive medicine practice among physicians in Egypt versus Saudi Arabia: causes and associated factors - Rana Adel; Mohammed Hassan Gaballah; Radwa Sehsah; Sara Ibrahim Sayed; Mostafa Mohammed Asem; Nada A. Yousri (Egyptian Journal of Forensic Sciences)
Abstract Background Defensive medicine (DM) is an international dilemma affecting developed and developing countries. Most research studies were conducted in high-income countries. Thus, the current study aimed to compare the attitudes and practices of DM among different specialty physicians practicing in Egypt and Saudi Arabia (KSA). Associated factors and causes of DM practice were also examined. This survey study is based on a self-administered online questionnaire consisting of seven domains that targeted physicians with different specialties and workplaces in Egypt and KSA. Results A total of 829 physicians completed the questionnaire. Physicians practicing in Egypt (31.4%) exhibited significantly higher rates of DM practice than those in KSA (13.2%). Regarding types of DM practice, 47% and 40% of all studied physicians practiced positive and negative DM, respectively, with significantly higher rates in Egypt than in KSA. Factors that predict DM practice were different among both countries; however, legal concerns are the basic factors that are significantly associated with positive and negative DM practice in both countries. Fear of legal concern is the main reason physicians practicing in Egypt use DM practice while following clinical standards and ethics is the main cause reported by those practicing in KSA. Conclusion Defensive medicine practices are prevalent among physicians in Egypt and KSA, with some differences between both countries in associated factors. Addressing physicians' legal concerns, improving medical education, and implementing evidence-based practices may help reduce unnecessary DM.